Mosquito Repellent and Physical Quality of Indoor Air as the Main Risk Factors for ARI Incidence in Toddlers (Case Study in the Balongsari Health Center) - Nafi’atul Irbah; Lestari, Anetya Martiadevi; Khuliyah Candraning Diyanah; Shamsul Bahari Shamsudin; Aditya Sukma Pawitra (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: The incidence of ARI in children under five in Balongsari Health Center saw a significant rise. The rise in ARI cases is attributed to air pollution, environmental contamination, and poor public hygiene. One of the causes of air pollution is the use of mosquito repellent. This study aimed to analyze risk factors associated with pollution sources, home physical conditions, and toddler characteristics related to ARI in the Balongsari Health Center area. Methods: This study uses quantitative approach with a case-control design, this study involved a sample of 50 toddlers in the case group and 50 in the control group, selected through simple random sampling. Data were collected via interviews and observation and analyzed using the Chi-Square test. The questionnaire covered toddler's characteristics, sources of indoor pollution, and physical household conditions. Temperature was measured with a thermohygrometer. Meanwhile, ventilation and room size were measured with a roll meter. Results and Discussion: Results indicated that mosquito repellent use was significantly associated with ARI (p = 0.010; OR = 4.000), along with physical conditions such as room temperature (p = 0.004; OR = 4.667), ventilation (p = 0.020; OR = 3.455), and household density (p = 0.032; OR = 3.286). Conclusion: These findings suggest that mosquito repellent selection, ventilation improvements, and breastfeeding practices play a crucial role in ARI prevention among toddlers in this area.